Application of the Picture And Picture Cooperative Learning Model in Class 3 Indonesian Language Learning in Elementary Schools: Penerapan Model Pembelajaran Kooperatif Picture And Picture pada Pembelajaran Bahasa Indonesia Kelas 3 di Sekolah Dasar - Sofiyanti, Fivy; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to identify and apply the picture and picture learning model in Indonesian class 3 learning at SDN Gununggangsir II. This study uses a descriptive qualitative approach with a phenomenological type. At the stage of data collection techniques used are interviews, observation, and documentation. The process of checking the validity of the data using the data analysis method according to Soejdono which consists of data reduction, data presentation, and drawing conclusions. The results of this study are that the picture and picture learning model is a learning model that can foster student enthusiasm and create an active, efficient, effective and fun learning process. This learning model is a learning model that is preferred by students, especially grade 3 students.